Interactive applications based on the shiny/r package to explain statistical concepts: A literature systematic mapping - Toledo San Martín, Álvaro; Vicencio Pardo, Inés (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Shiny is an application for R software that allows the creation of interfaces for users without programming knowledge. In this work we use a systematic mapping method for the collection, analysis, and extraction of information in publications that indicate the use of Shiny to explain statistical concepts. Among the conclusions, it is found that Shiny is used as a tool for carrying out academic experiences, as well as a means for solving problems in the areas of education and natural and life sciences, addressing statistical topics related to pre-inferential statistics and inferential statistics, among others.